Using froth flotation to mitigate acid rock drainage risks while recovering valuable coal from ultrafine colliery wastes - Mbamba, Christian Kazadi (Centre for Bioprocess Engineering Research, 2015)
This dissertation presents the results of an investigation to develop a two-stage flotation process to produce: (i) a low-volume sulfide-rich concentrate that can be treated chemically or biologically or disposed of in a contained manner; (ii) a high-volume (low sulfur) benign tailings, with low ARD potential compared to conventional tailings; and (iii) a coal concentrate that has added value on account of its low sulfur and ash content. Success requires integration of flotation, aqueous chemistry and mineral bioleaching expertise. The approach adopted in this exploratory study entails coal flotation in the first stage, which takes advantage of its natural hydrophobicity.